Alphabet of ‘Spaces-between’. Similarities and Changes of In-between Places (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2025)
The urban analysis of highly historicised fabrics is not always immediately intelligible, especially when one seeks a spatial dimension so rarefied and lacking in clear definition that it becomes difficult to categorise - like that of ‘in-between’ places. The space in between - between things - is the place of connections, where the focus of investigation shifts to relationships that transcend material architecture, while still implicitly acknowledging its existence. In exploring this theme, it becomes necessary to draw on literature that, even if only marginally, addresses this field of inquiry. As a result, it is obvious to come across a large number of definitions which attempt to connote the same concept, though each defining it with a different nuance. An ambiguous, ephemeral, immaterial concept. The aim of this research is therefore to trace the infra-structure as a constituent part of a complex fabric and as a component through which “we manufacture the image of reality” (Wittgenstein 1967: 177). Certainly not as a simple or simplified given, but as an elementary moment - and therefore node - in which maximum complexity is condensed. Considerations regarding urban phenomena of this type make it possible to include within the city these new contemporary territories which, rejecting such dichotomous mechanisms, work on unifying aspects and organisms, and thus on areas of relation, which find their fertile ground in the in-between of the city. The research, starting from the re-reading of the surveys of two cities facing the Mediterranean, makes use of operations of deconstruction, enumeration, and comparison, in order to define new repertoires for reading the city - starting from the in-between, intended as places that oppose a dominant culture of ‘full architecture’, that is, the predominance of the built environment over the incidence of interruptions.
Keywords: archetypes; urban eidotypes; urban morphology